2016
DOI: 10.1002/bab.1318
|View full text |Cite
|
Sign up to set email alerts
|

Cell growth behaviors of Clostridium acetobutylicum in a pervaporation membrane bioreactor for butanol fermentation

Abstract: Acetone-butanol-ethanol fermentation using Clostridium acetobutylicum was studied in the continuous and closed-circulating fermentation (CCCF) system. The experiment lasting for 192 H was carried out by integrating fermentation with in situ pervaporation. In the entire process, the cell growth profile took place in the following two phases: the logarithmic phase during early 28 H and the linear phase from 130 to 150 H. This was a unique characteristic compared with the curve of traditional fermentation, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 24 publications
0
8
0
1
Order By: Relevance
“…For example, for an initial glucose concentration of 6 g/L (33.3 mmol/L), μ max was 0.32 and 0.29 h −1 and 0.23–0.2 h −1 for C. beijerinckii NCIMB8052 (ATCC51743) and C. beijerinckii SA‐1 (ATCC35702) cultivated in reinforced clostridium media (RCM) and sweet sorgun syrup juice (SSSJ), respectively . Yao et al reported higher μ max , 0.345 h −1 , for C. acetobutylicum CICC 8012 cultivated at an initial glucose concentration of 60 g/L (333.3 mmol/L). The μ max values were reached when the pH was ∼5.8–6.3 (Figure b).…”
Section: Resultsmentioning
confidence: 99%
“…For example, for an initial glucose concentration of 6 g/L (33.3 mmol/L), μ max was 0.32 and 0.29 h −1 and 0.23–0.2 h −1 for C. beijerinckii NCIMB8052 (ATCC51743) and C. beijerinckii SA‐1 (ATCC35702) cultivated in reinforced clostridium media (RCM) and sweet sorgun syrup juice (SSSJ), respectively . Yao et al reported higher μ max , 0.345 h −1 , for C. acetobutylicum CICC 8012 cultivated at an initial glucose concentration of 60 g/L (333.3 mmol/L). The μ max values were reached when the pH was ∼5.8–6.3 (Figure b).…”
Section: Resultsmentioning
confidence: 99%
“…The commonly used ABE recovery processes are distillation, adsorption, gas tripping, and liquid-liquid extraction, perstraction and pervaporation. The advantages and disadvantages of different purification method of ABE are shown in Table 4, while the comparison between the purification method are shown in Table 5 [91][92][93][94][95][96][97][98][99][100][101][102].…”
Section: Products Separation and Recoverymentioning
confidence: 99%
“…Researchers have also investigated reactor designs that can selectively remove the desired product from the reactor broth through selectively permeable membranes . Specialized membrane reactors focused on the process of pervaporation, or the removal of a product via partial vaporization through a membrane in the bioreactor, have been considered for systems where volatile renewable liquid biofuels are produced . San and Stephanopoulos investigated the use of fed‐batch systems to maximize the productivity of penicillin production .…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] Specialized membrane reactors focused on the process of pervaporation, or the removal of a product via partial vaporization through a membrane in the bioreactor, have been considered for systems where volatile renewable liquid biofuels are produced. [15][16][17] San and Stephanopoulos investigated the use of fed-batch systems to maximize the productivity of penicillin production. 18 Warikoo et al exemplified the use of continuous perfusion reactors for the production of therapeutic proteins from Chinese hamster ovary (CHO) cells.…”
Section: Introductionmentioning
confidence: 99%